Collaborative Governance for Strengthening Children's Civil Rights and Freedoms in Bogor Regency - Iman Kristiani Lahagu; Kusworo Kusworo; Rizki Amalia (Sean Institute, 2026)
The fulfillment of children's civil rights and freedoms as part of Cluster I of the Child-Friendly Regency (KLA) policy requires the involvement of multiple stakeholders through collaborative governance. However, Bogor Regency continues to face several challenges, including the low ownership rate of Child Identity Cards (KIA), disparities in birth certificate and KIA ownership across districts, limited availability of child-friendly information facilities, and uneven child participation through Child Forums. Although various coordination forums and KLA institutional mechanisms have been established, the achievement of children's civil rights and freedoms remains uneven across regions. This condition indicates a gap between the collaborative governance framework that has been formally established and its implementation in practice. This study aims to analyze collaborative governance in strengthening children's civil rights and freedoms in Bogor Regency using a qualitative approach and the collaborative governance framework developed by Ansell and Gash, consisting of starting conditions, institutional design, facilitative leadership, and collaborative process. Data were collected through in-depth interviews, observation, documentation, and secondary data analysis. The findings reveal that collaborative governance has been implemented but remains largely at a coordinative stage and has not yet evolved into an integrative and deliberative form of cross-sector collaboration. The study concludes that strengthening children's civil rights and freedoms in Bogor Regency requires more integrative, participatory, and sustainable collaborative governance mechanisms.